Analysis of an improved Cyanophora paradoxa genome assembly. (16th May 2019) - Price, Dana C; Goodenough, Ursula W; Roth, Robyn; Lee, Jae-Hyeok; Kariyawasam, Thamali; Mutwil, Marek; Ferrari, Camilla; Facchinelli, Fabio; Ball, Steven G; Cenci, Ugo; Chan, Cheong Xin; Wagner, Nicole E; et al.
Abstract: Glaucophyta are members of the Archaeplastida, the founding group of photosynthetic eukaryotes that also includes red algae (Rhodophyta), green algae, and plants (Viridiplantae). Here we present a high-quality assembly, built using long-read sequences, of the ca. 100 Mb nuclear genome of the model glaucophyte Cyanophora paradoxa . We also conducted a quick-freeze deep-etch electron microscopy (QFDEEM) analysis of C. paradoxa cells to investigate glaucophyte morphology in comparison to other organisms. Using the genome data, we generated a resolved 115-taxon eukaryotic tree of life that includes a well-supported, monophyletic Archaeplastida. Analysis of muroplast peptidoglycan (PG) ultrastructure using QFDEEM shows that PG is most dense at the cleavage-furrow. Analysis of the chlamydial contribution to glaucophytes and other Archaeplastida shows that these foreign sequences likely played a key role in anaerobic glycolysis in primordial algae to alleviate ATP starvation under night-time hypoxia. The robust genome assembly of C. paradoxa significantly advances knowledge about this model species and provides a reference for exploring the panoply of traits associated with the anciently diverged glaucophyte lineage.